Reconnecting the city : the historic urban landscape approach and the future of urban heritage - Bandarin, Francesco; Oers, Ron van, 1965-; Bandarin, Francesco (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2015)
'The Historic Urban Landscape aims to respect and celebrate diversity--of heritage resources and cultural traditions'--
'Historic Urban Landscape is a new approach to urban heritage management, promoted by UNESCO, and currently one of the most debated issues in the international preservation community. However, few conservation practitioners have a clear understanding of what it entails, and more importantly, what it can achieve. Following the publication of The Historic Urban Landscape : Managing Heritage in an Urban Century, the approach is now further elaborated with a more practical slant and translates the notion into an operational set of management practices. In this follow-up book, the editors pull together specially commissioned chapters on best practice in urban heritage management from established professionals in the field. Drawn from a variety of disciplines related to urban management and conservation these authors present and discuss methodologies and practices to consider in the implementation of the Historic Urban Landscape approach as advocated by UNESCO. The contributors are selected from professionals who have written, argued or debated about the role of historic cities in contemporary society. As well as their chapters, there are interviews with six high-profile people from different regions of the world giving their critical reflections on the UNESCO approach in relation to their own ideas on urban heritage conservation and city management. Reconnecting the City : the Historic Urban Landscape Approach and the Future of Urban Heritage provides a thorough discussion, structured by themes on issues related to key topics in the field of urban management, from changing demographics and increasing urbanisation to the pressures of economic development and decentralisation; social interaction; and economic feasibility and financing of heritage conservation. By presenting a range of methodologies and tools to support urban conservation in a way that is sensitive to cultural differences, the editors encourage a departure from the compartmentalized approaches of today's urban heritage management. The book includes contributions from HH The Aga Khan, Rem Koolhaas, Stefano Bianca and Julian Smith--and many other internationally respected figures. The book's companion website offers invaluable resources from UNESCO relating to the Historic Urban Landscape Approach, as well as additional illustrations and web-links'--
Preface / Francesco Bandarin and Ron van Oers -- Introduction: Urban Conservation and the End of Planning / Francesco Bandarin -- SECTION 1. The Layered Dimensions of Urban Conservation -- Archaeology : Reading the City through Time / Tim Williams -- How Geology Shapes the Urban Environment / Claudio Margottini and Daniele Spizzichino -- Morphology as the Study of City Form and Layering / Stefano Bianca -- Interview: Searching for a Chinese Approach to Urban Conservation / Wang Shu -- Case study: Bologna : From Urban Restoration to Urban Rehabilitation / Patrizia Gabellini -- Historic Cities and Climate Change / Anthony Gad Bigio -- Interview: Looking at the Challenges of the Urban Century / Filipe Duarte Santos -- The Intangible Dimension of Urban Heritage / Rohit Jigyasu -- Interview: Interpreting Cultural Landscapes as Expressions of Local Identity / Lisa Prosper -- Case study: The Traditional Chinese View of Nature and Challenges of Urban Development / Feng Han -- Planning and Managing Historic Urban Landscapes / Francesco Siravo -- Interview: The Challenge of Urban Transformation / Mohsen Mostafavi -- Cities as Cultural Landscapes / Ken Taylor -- SECTION 2. Building the Toolkit -- Evolution of the Normative Framework / Jukka Jokilehto -- Civic Engagement Tools for Urban Conservation / Julian Smith -- Interview: Listening to the People, Promoting Quality of Life / His Highness the Aga Khan -- Case study: Valuing Cultural Diversity / Richard Engelhardt -- Knowledge and Planning Tools / Jyoti Hosagrahar -- Case study: Reading the City of Tokyo / Hidenobu Jinnai -- The Role of Regulatory Systems / Patricia O'Donnell -- Interview: Constructing Cultural Significance / Rahul Mehrotra -- Devising Financial Tools for Urban Conservation / Donovan Rypkema -- Case study: A User's Guide for Heritage Economics / Christian Ost -- Case study: The World Bank's Tools for Urban Conservation / MV Serra -- Researching and Mapping the Historic Urban Landscape / Michael Turner and Rachel Singer -- Interview: Heritage and the Metropolis / Rem Koolhaas -- Conclusion: The Way Forward : An Agenda for Reconnecting the City / Ron van Oers -- Contributors.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Historic buildings -- Conservation and restoration; Historic sites -- Conservation and restoration; Historic districts -- Conservation and restoration; Cities and towns -- Conservation and restoration; Urban landscape architecture -- Conservation and restoration; Cultural landscapes -- Conservation and restoration; Historic preservation; City planning; Cultural policy; Urban policy; Historic buildings -- Conservation and restoration; Historic districts -- Conservation and restoration; Historic sites -- Conservation and restoration; Electronic books